Information and Communication Technologies in Tourism 2018 2017
DOI: 10.1007/978-3-319-72923-7_22
|View full text |Cite
|
Sign up to set email alerts
|

Technology Empowered Real-Time Service

Abstract: Real-time service has gained higher importance as part of the digital competitiveness of brands. This has followed the establishment of social media as an engagement mechanism that supports consumer experience by bridging consumer expectations and brand performance in real time. The ubiquity of social media's constant connectivity has led to the increasing demand of instant gratification. Consumers not only demand brands to provide a personalised response, but also expect them to reply instantly 'now'. This ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…The respondent also intimated that a robot might serve as a good intermediary between the human staff and the customer (Chung and Cakmak, 2018). This finding is consistent with another exploratory study that sought to understand how technology may positively impact a company with real-time service response (Sinarta and Buhalis, 2018). This research demonstrated that real-time service facilitates co-creation abilities and fosters engagement (Sinarta and Buhalis, 2018).…”
Section: Customer Satisfaction Training and Service Recoverysupporting
confidence: 89%
“…The respondent also intimated that a robot might serve as a good intermediary between the human staff and the customer (Chung and Cakmak, 2018). This finding is consistent with another exploratory study that sought to understand how technology may positively impact a company with real-time service response (Sinarta and Buhalis, 2018). This research demonstrated that real-time service facilitates co-creation abilities and fosters engagement (Sinarta and Buhalis, 2018).…”
Section: Customer Satisfaction Training and Service Recoverysupporting
confidence: 89%
“…Compression of time requires the acquisition and use of information based decision-making, initiating action, deployment of resources and ultimately innovation within time constraints (McKenna, 1997). This simultaneously accelerates the relationship between organizations and customers in cocreation and creates enormous opportunities for value creation (Sinarta & Buhalis, 2018).…”
Section: Real Time Tourism Managementmentioning
confidence: 99%
“…The five‐item scales for measuring convenience motivation were adapted from Farquhar and Rowley (2009). Real‐time customer service was measured using four‐item scales based on Sinarta and Buhalis (2018), adapted to suit consumers' motivation for watching live‐streaming marketing sessions. consumer–brand relationship quality was assessed using four‐item scales adapted from Park and Stoel (2005).…”
Section: Methodsmentioning
confidence: 99%